Case report: Clinical, genetic and immunological characterization of a novel XK variant in a patient with McLeod syndrome - Dambietz, Christine Anna; Doescher, Andrea; Heming, Michael; Schirmacher, Anja; Schlüter, Bernhard; Schulte-Mecklenbeck, Andrea; Thomas, Christian; Wiendl, Heinz; Meyer zu Hörste, Gerd; Wiethoff, Sarah (Frontiers in Genetics, 2024)
Introduction Pathogenic variants in the XK gene are associated with dysfunction or loss of XK protein leading to McLeod syndrome (MLS), a rare X-linked neuroacanthocytosis syndrome with multisystemic manifestation. Here we present clinical, genetic and immunological data on a patient originally admitted to our clinic for presumed post-COVID-19 syndrome, where thorough clinical work-up revealed a novel frameshift deletion in XK causal for the underlying phenotype. We additionally review the clinicogenetic spectrum of reported McLeod cases in the literature. Methods We performed in-depth clinical characterization and flow cytometry of cerebrospinal fluid (CSF) in a patient where multi-gene panel sequencing identified a novel hemizygous frameshift deletion in XK. Additionally, Kell (K) and Cellano (k) antigen expression was analysed by Fluorescenceactivated Cell Sorting (FACS). KEL gene expression was examined by RNA sequencing. Results A novel hemizygous frameshift deletion in the XK gene resulting in premature termination of the amino acid chain was identified in a 46-year old male presenting with decrease in physical performance and persisting fatigue after COVID-19 infection. Examinations showed raised creatine kinase (CK) levels, neuropathy and clinical features of myopathy. FACS revealed the K-k+ blood type and reduced Cellano density. CSF flow cytometry showed elevation of activated T cells. Conclusion In-depth clinical, genetic, immunological and ribonucleic acid (RNA) expression data revealed axonal neuropathy, myopathy and raised levels of activated CSF-T-lymphocytes in a patient with a previously unpublished frameshift deletion in the XK gene.